Mon portrait par Bonnat : imaginaire scénique de l’homme politique républicain - Florence Fix (Quêtes Littéraires, 2015)
Before World War 1, French painter Léon Bonnat became famous by portraying celebrities, among which almost every leading politician in the newly founded Republic. His academic and dark style however was criticized by art critics and humourists; hence his portraits put on stage in character comedies have to be read as critics of the very people they represent and of himself as an official artist.